What do Cochrane systematic reviews say about interventions for vitamin D supplementation? - Mateussi, Mariana Vendramin; Latorraca, Carolina de Oliveira Cruz; Daou, Júlia Pozetti; Martimbianco, Ana Luiza Cabrera; Riera, Rachel; Pacheco, Rafael Leite; Pachito, Daniela Vianna (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Despite the high prevalence of vitamin D supplementation, its use remains controversial. The objective of this review was to identify and summarize the evidence from Cochrane systematic reviews regarding vitamin D supplementation for preventing or treating any clinical condition. DESIGN AND SETTING: Review of systematic reviews, conducted in the Discipline of Evidence-Based Medicine, Escola Paulista de Medicina, Universidade Federal de São Paulo. METHODS: A search was conducted to identify all Cochrane systematic reviews that fulfilled the inclusion criteria. Titles and abstracts were screened by two authors. RESULTS: We included 27 Cochrane systematic reviews: 10 assessing use of vitamin D for prevention and 17 for treatment. The reviews found moderate to high quality of evidence regarding the benefit of vitamin D for pregnant women (prevention of adverse events: preterm birth risk [rate ratio, RR 0.36; 95% confidence interval, CI 0.14 to 0.93] and low birthweight risk [RR 0.40; 95% CI 0.24 to 0.67]) and for asthma patients (reduction of severe exacerbations [RR 0.63; 95% CI 0.45 to 0.88]). No benefit was found regarding vitamin D supplementation alone (without calcium) for preventing hip or any new fracture. For all other outcomes assessed under various conditions, the current quality of evidence is low or unknown, and therefore insufficient for any recommendation. CONCLUSION: Based on moderate to high quality of evidence, the Cochrane systematic reviews included here showed that there were some benefits from vitamin D supplementation for pregnant women and asthma patients and no benefits for preventing fractures.